Comparison of the Huggins band for six ozone isotopologues: vibrational levels and absorption cross section - Ndengué, Steve; Meyer, Hans-Dieter (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2012)
By use of the 31A′ ab initio potential energy surface (PES) of ozone and the multi-configuration time-dependent Hartree program for wavepacket propagation, we have determined numerous eigenstates of this state for six ozone isotopologues. These bound vibrational levels are the upper levels of the Huggins band, which covers the range from 27 000 to ∼33 000 cm-1. This study extends our previous work on the Hartley band, which was limited to the range ∼32 000-50 000 cm-1. Four isotopologues, 16O3, 16O17O16O, 16O18O16O, and 18O3 (noted hereafter 666, 676, 686, and 888), are symmetric, and two are asymmetric, 17O16O2 and 18O16O2 (noted hereafter 667 and 668). The PES of the 31A′ state has two equivalent minima of Cs symmetry located at ∼27 000 cm-1 above the X1A1 ground state. The equilibrium geometry of these two minima is re1 = 2.28 a0, re2 = 3.2 a0, and θe = 107°. The dissociation limit of this PES, which correlates to the O(1D) + O2 (1Δ) “singlet” channel, is about 4300 cm-1 above the two minima. For the 16O3 isotopologue, the 120 lowest bound eigenstates have been calculated and partially assigned up to 800 cm-1 below the dissociation limit. The 60 lower eigenstates are easily assignable in term of three normal modes, the “long” bond (ν1), the bending (ν2), and the “short” bond (ν3). A new family of wave functions, aligned along the dissociation channels, appears at 3782 cm-1 above the 31A′ (0,0,0) level. The 31A′ vibrational levels and the corresponding intensity factors from the (000), (010), (100), and (001) levels of the X1A1 ground state have been calculated for the six isotopologues. The Huggins absorption cross sections of the six isotopologues have been calculated from the 31A′ vibrational energy levels and the corresponding intensity factors. The rotational envelope of each vibronic band has been empirically described by an ad hoc function. The ratio of the Huggins cross section of each ozone isotopologue with one of 16O3 provides the fractionation factor of each ozone isotopologue as a function of the photon energy. These various fractionation factors will allow predicting enrichments due to photolysis by various light sources like the actinic flux.